1992
DOI: 10.3109/15513819209024212
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Cerebral Vasculopathy in an Infant: Clinical, Neuroradiographic, and Neuropathologic Studies

Abstract: An infant with neurofibromatosis developed recurrent cerebrovascular accidents beginning at 3 months of life. Cerebral arteriography demonstrated large-vessel occlusive disease and bilateral severe moyamoya. At autopsy these lesions were apparent on gross examination, and advanced intimal and medial dysplasia was seen on microscopic examination of both the anterior and posterior circulations. Although rare, neurofibromatosis cerebrovasculopathy may occur in young infants and may account for some strokes in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…20,[33][34][35][36] The authors suggested that the neurofibromatosis type I protein is responsible for the growth of endothelial and smooth muscle cells in the ICA and their branches. Although this presumption could not be confirmed, several indications for a MMD gene on Chromosome 17q25 were found.…”
Section: Acta2mentioning
confidence: 99%
“…20,[33][34][35][36] The authors suggested that the neurofibromatosis type I protein is responsible for the growth of endothelial and smooth muscle cells in the ICA and their branches. Although this presumption could not be confirmed, several indications for a MMD gene on Chromosome 17q25 were found.…”
Section: Acta2mentioning
confidence: 99%
“…6 More than 50 cases of such an association have been reported so far. 4,[7][8][9] In the present study, we conducted linkage analyses on pedigrees of familial moyamoya disease to test the hypothesis that moyamoya disease is linked to a particular chromosomal region. …”
mentioning
confidence: 99%
“…Stenotic/occlusive disorder of intracranial vascular supply generally presents symptoms in childhood or adolescence, being eventually the first manifestation of NF1 in children 11 . More rarely, cases in individuals older than 40 were described 10 .…”
Section: Discussionmentioning
confidence: 99%